2018
DOI: 10.1016/j.ajpath.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The Early Innate Immune Response to, and Phagocyte-Dependent Entry of, Cryptococcus neoformans Map to the Perivascular Space of Cortical Post-Capillary Venules in Neurocryptococcosis

Abstract: The innate immune system is the primary defense against cryptococcal infection, but paradoxically it promotes infection of the central nervous system. We performed a detailed longitudinal study of neurocryptococcosis in normal, chimeric, green fluorescent protein phagocyte-positive mice and phagocyte-depleted mice and interrogated the central nervous system innate immune response to Cryptococcus neoformans H99 using confocal microscopy, histology, flow cytometry, and quantification of brain cytokine/chemokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…2B). It is possible that the detected yeast burden is arrested in the small capillaries (2326), or in the post-capillary venules (27) and has not yet invaded the brain parenchyma. However, this is consistent with invasion of the brain since upon arrest in capillaries, C. neoformans quickly crosses endothelial barriers (24) and possibly the blood brain-barrier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B). It is possible that the detected yeast burden is arrested in the small capillaries (2326), or in the post-capillary venules (27) and has not yet invaded the brain parenchyma. However, this is consistent with invasion of the brain since upon arrest in capillaries, C. neoformans quickly crosses endothelial barriers (24) and possibly the blood brain-barrier.…”
Section: Resultsmentioning
confidence: 99%
“…We detected no yeasts in the circulating blood of mice, which raises a question of how the bloodstream is so quickly invaded and quickly cleared. Other groups observed that in IV infection fungi are cleared from the bloodstream in hours or the day after infection (27, 35), with fungemia only resurfacing very late in the infection. These observations, together with ours, imply that yeast transit time in blood is very short (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. neoformans can enter the brain through direct invasion of the brain endothelial cells [21][22][23][24][25], evidence has been provided that mononuclear phagocytes promote brain invasion of the organism [21,26,27]. C. neoformans can survive in monocytes [28,29], and monocytes containing C. neoformans have been found present in the perivascular space of the brain [23,27]. Intravenous administration of C. neoformans-infected macrophages can enhance the brain fungal burden [26], while depletion of monocytes can reduce the brain fungal burden [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…C. neoformans can survive in monocytes [28,29], and monocytes containing C. neoformans have been found present in the perivascular space of the brain [23,27]. Intravenous administration of C. neoformans-infected macrophages can enhance the brain fungal burden [26], while depletion of monocytes can reduce the brain fungal burden [26,27]. Notably, monocytes harboring C. neoformans have been directly seen to cross a monolayer of brain endothelial cells cultured in vitro [30,31].…”
Section: Introductionmentioning
confidence: 99%